POSSIBILITIES OF THE EFFICIENT SOLID-LIQUlD SEPARATION IN THE HYDROCYCLONE OF 25 mm DIAMETER - Branko Salopek; Suzana Filipović; Dragan Krasić (Rudarsko-geološko-naftni Zbornik, 1995)
The hydrocyclone, of 25 mm diameter has been tested on the laboratory hydrocyclonic device. There have been varied the values of relationship between Du/Do the concentration of feed suspension and the greatness of pressure. With thc suspension of fine grindeed limestone and water there have been examined 36 combinations of various values for the mentioned variables, The optimal efficiency of the liquid in overflow has been achieved hy the relationship Du/Do=0.73 ranging from 70...80 % with the concentration of the solids in overflow from 0.3..1.5 % and cut size of 0.004...0.006 mm. There have been shown three schemes of separation of drilling fluids proposing the application of multicyclones instead of centrifuges in the final phase of cleaning the fluids